Una aproximación a la evaluación del imaginario del turismo en las ciudades del conocimiento - Osuna, Jesús Manuel Fitch (Diálogos Latinoamericanos, 2013)
The study asserts the image of urban tourism that develops in the cities where the main economic activity tends to be generating and applicating knowledge.The article describes the type of knowledge encountered in the city, identifying the relevant elements of the urban dynamics. The case study is Monterrey in Mexico where the focus is specifically on the urban and pop performances and strategies for developing tourism activities, the "Project of Saint Lucia - Urban Integration". The article focuses on two methods. First contemplative observation about the site and its urban environment, then structured interviews with the users of this public space. The article identifies morphological elements that make up the image of Monterrey, which contrast the basic idea of Monterrey.